A 20‐year data set of species replacement patterns in the middle‐intertidal zone of Tatoosh Island, Washington, USA. Issue 3 (March 2016) - Wootton, J.Timothy
Abstract: This data set documents changes in the sessile species occupying several rock benches on wave‐exposed shores of Tatoosh Island, Washington, USA from 1993 to 2012. Plots and transects were located within the middle intertidal zone dominated by the mussel Mytilus californianus . Data were taken in 14 60 × 60 cm quadrats positioned at two corners with permanent marking screws. A 10 × 10 grid defined by the intersection of equally spaced monofilament lines yielded a set of 100 fixed points per quadrat per census. Plots were generally located initially in sites that had undergone natural wave disturbance in the past 0–3 years, to better document transient successional dynamics, and most plots have experienced one or two disturbance/succession cycles over the course of the data collection. A further set of points was monitored on 11 permanent transects 9.1 m long with 30 initially randomly placed points, which cover a broader span of shoreline than the quadrats. The data collection was implemented to parameterize Markov Chain models and use these to make predictions about the effects of local species extinction that could subsequently be tested in an experimentally tractable ecosystem. To date, the data have been used in (1) a parameterization and analysis of a basic multi‐species Markov Chain model, (2) a spatially explicit cellular automata, (3) a reformulation, parameterization, and experimental test of the Neutral Theory of Biodiversity, (4) a comparative analysis of Markov Chain models across different marine habitats, (5) development of an approach to link global change to multi‐species interactions using an environment‐dependent (ocean acidification) series of Markov Chain models, (6) analysis of changes in system dynamics following experimental species extinction, and (7) parameterization of population dynamic models of mussels revealing density‐linked stochastic patterns. The Markov Chain and Neutral models have subsequently been tested in independent experiments. These data may be of further use in analyzing detailed patterns of species transitions, as well as more standard analyses of spatial and temporal patterns of species abundance and richness.